Alternativas para la reducción de Fusarium sp en el cultivo de alelí ( Matthiola incana), utilizando técnicas de control fitosanitario establecidas en la finca Gemmolles S.A., Cotopaxi. - Albán Santana, Alex Mauricio (2021)
Fusarium sp causes the most important disease in the greenhouse cultivation of stock because it originates the mortality of the transplanted plants, mainly in their fírst phenological stages; these losses are more critical during the first four weeks of the cycle; therefore, in mortality records, they exceed 10% of the affected population. In the phytosanitary management of the crop, control techniques have been established, the fírst one through Chemical producís application whose active ingredients are: Fosetyl aluminum, Iprodione, Captan, and Hymexasol; the second one through products of a biological nature application: Trichoderma sp and Bacillus subtilis; the third one with the use of antibiotics: Pyrocontrol of weeds, Kasugamycin, Polioxyn B, Azoxystrobin, and Kresoxym methyl; and the plantation program that is an association of products of the techniques mentioned above: Fosetyl aluminum, Bacillus subtilis. Polioxyn B, Hymexasol, and Azoxystrobin. The control efficacy was measured by the severity Índex of the fungus in the crop, regarding the mortality, the loss índex. The statistical model was a completely randomized block design, with three repetitions and five treatments; the data were collected with a frequency of 8 days and the phytosanitary applications with a frequency of 15 days during 10 weeks of the cycle; for the evaluation follow-up, a universe of 100 random plants was established where 10 plants were evaluated by the plantation method on a scale of two levels of infection with four degrees of affection each one; and, the mortality that Fusarium sp. The scientifíc verification of Fusarium sp was made through the biological laboratory results of "Agrocalidad," using the PCR technique in soil isolation and plant tissue. At the end of the experimentation, the lowest average was the plantation treatment with 13.77% mortality, while the absolute control had 63.00% mortality. This study seeks to provide guidance on the most effective control technique to be used as an alternative to reduce fusarium populations in crops of the Brassicaceae family, especially in Matthiola incana, stock.